PENGARUH TEKNIK SELF CONTROL UNTUK MENGATASI PERILAKU AGRESIF SISWA MELALUI BIMBINGAN KELOMPOK DI SMP NEGERI 9 PEKANBARU - Diera Sintia; Raja Arlizon; Siska Mardes (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Aggressive behavior is a behavior intended to hurt other people both physically and verbally in order to hurt others. Aggressive behavior can be demonstrated through various forms of behavior, such as attacking other people (hitting, slapping, kicking, biting), threatening physically or verbally, harassing others (mocking, shouting, saying rude), anger (irritability, revenge), feeling of entrepreneurship (bad prejudice, jealousy) being impolite and compelling to possess other people's things that are not his. One way to overcome aggressive behavior is to use self control techniques. The purpose of this study was to describe the aggressive behavior of students before and after being given the technique of self control through group guidance, to determine differences in aggressive behavior of students before and after self control techniques through group guidance and to determine the effect of self control techniques through group guidance to overcome behavior aggressive students. This research is an experimental quantitative research with one group pre-test post-test approach. The subjects in this study were 7 students taken by purposive sampling technique with questionnaire results. The results showed that: (1) The aggressive behavior of students before being given the technique of self control was in the high category, the aggressive behavior of students after being given the technique of self control was mostly in the low category. (2) There is a significant difference between the aggressive behavior of students before and after being given the technique of self control. (3) There is a significant effect of the technique of self control on students' aggressive behavior.Key Words: Self Control, Aggressive Behavior, Group Guidance